The Independent and Joint Effects of Different Childhood Abuse Types on Subjective Prospective and Retrospective Memory Impairment During Pregnancy - Zhang, Xuan; Wu, Liuliu; Wang, Juan; Mao, Fangxiang; Sun, Jiwei; Cao, Danfeng; Cao, Fenglin (Frontiers in Psychology, 2021)
Background and Objective: Childhood abuse is considered a risk factor in various health outcomes during pregnancy. However, no study has explored the relationship between childhood abuse and memory impairment during pregnancy. This study is the first to explore the relationship between childhood abuse and subjective memory impairment. Participants, Setting, and Methods: A total of 1,825 pregnant women were recruited from a comprehensive hospital in Shandong province, China, and completed a questionnaire survey. Multivariable linear regression analysis was used to explore the relationship between childhood abuse and subjective prospective and retrospective memory. Results: Pregnant women with high total childhood abuse scores had high prospective and retrospective memory impairment. Among pregnant women reporting only emotional abuse, only physical abuse, or only sexual abuse, women reporting only emotional abuse were found to have high prospective and retrospective memory impairment. Women with all three childhood abuse types also had high prospective and retrospective memory impairment. Conclusion: Women who experienced childhood abuse, especially childhood emotional abuse, had high subjective memory impairment during pregnancy. It is important to ask pregnant women about their experiences of childhood abuse, especially emotional abuse, during early prenatal care, as such abuse is likely to have negative effects on memory during pregnancy.